The Labor Market Integration of Refugees to the United States: Do Entrepreneurs in the Network Help? - Olivier Dagnelie; Anna Maria Mayda; Jean Francois Maystadt (Institute of Labor Economics (IZA), 2018)
We investigate whether entrepreneurs in the network of refugees - from the same country of origin - help refugees' labor-market integration by hiring them in their businesses. We analyze the universe of refugee cases without U.S. ties who were resettled in the United States between 2005 and 2010. We address threats to identification due to sorting of refugees into specific labor markets and to strategic placement by resettlement agencies. We find that the probability that refugees are employed 90 days after arrival is positively affected by the number of business owners in their network, but negatively affected by the number of those who are employees. This suggests that network members who are entrepreneurs hire refugees in their business, while network members working as employees compete with them, consistent with refugees complementing the former and substituting for the latter.
Keywords: F22; J61; 330; refugees; labor market integration; entrepreneurship